Hematoma of the liver from trauma closed abdomen. Experience with a conservative strategy - Trostchansky, julio L; Ruso, Luis; Vázquez, Aníbal; Trostchansky, José (Cirugía del Uruguay, 2003)
Liver traumatisms constitute a complex therapeutic problem. Within the last few years, the development of modem scanning procedures and patient control have rendered possible improvement in diagn9sis and evolutive follow-up of liver contusions, thus favoring a nonsurgical therapeutic approach in carefully selected patients. The purpose of this study is to evaluate selection parameters and evolutive control which are considered the efficient variables for non-surgical treatment of traumatic liver hematoma.